Comparison of the Effectiveness of Lavender and Rose Aromatherapy in Reducing Emesis Gravidarum Symptoms among First-Trimester Pregnant Women - Sukmawati; Dudeh Dewangsih; Novi Kristi Heriati; Resa Nurdewi Alawiyah; Nopiyanti; Tasmi (Jurnal Penelitian Pendidikan IPA, 2025)
Nausea and vomiting, or emesis gravidarum, is one of the early symptoms commonly experienced by pregnant women during the first trimester and can cause stress and mood disturbances. Non-pharmacological treatment that can be done includes aromatherapy, such as lavender and rose, to help reduce the symptoms felt by pregnant women. This study aims to compare the effectiveness of lavender aromatherapy and rose aromatherapy in reducing the symptoms of emesis gravidarum in pregnant women in the first trimester in Karawang Regency. This research method used a quasi-experimental design with two intervention groups, namely the administration of lavender aromatherapy and rose aromatherapy. The sample of this study was 130 pregnant women in the first trimester with symptoms of emesis gravidarum. The results of the statistical test showed a p-value = 0.001 (<0.05) for lavender aromatherapy and p-value = 0.003 (<0.05) for rose aromatherapy, which shows that both types of aromatherapies have significant effectiveness in reducing the symptoms of emesis gravidarum. Lavender and rose aromatherapy work through the olfactory system that affects the brain's limbic system, which can help relieve negative emotions such as anxiety and stress, which often trigger or worsen symptoms of emesis gravidarum. The mechanism of action of this aromatherapy provides a relaxing effect, where rose essential oil can stimulate the brain's limbic system**, which plays a role in regulating emotions and the body's response to stress.